AB1300 Ultrasound analysis of achilles enthesis erosions recovery capacity in spondyloarthritis. (23rd January 2014) - Parisi, S.; Lagana', A.; Ambrogio, F.; Bruzzone, M.; De Giovanni, R.; Centanaro Di Vittorio, C.; Peroni, C.L.; Scarati, M.; Fusaro, E.
Abstract : Background: Spondyloarthritis (SpA) is characterised by the inflammatory involvment of the enthesis. In the last few years, several studies have provided relevant data on the advantages and validity of using ultrasound (US) to study enthesis in SpA. Objectives: To evaluate with ultrasound the presence of erosions in Achilles tendons enthesis and their recovery capacity, in spondyloarthritis (SpA). Methods: A prospective study of Achilles enthesis erosions in SpA was undertaken. US and X-Ray examinations were performed at baseline and at 6 and 12 months of follow-up. Clinical outcomes measures were collected. Results: Bilateral Achilles enthesis of 45 patients (30 men, 15 women) were investigated. The mean C reactive protein (CRP) levels were 9, 9±6, 9 mg/L. US visualised 14 erosions (6, 3%) in 12 patients. X-Ray 11 erosions in 11 patients (4, 9%). At 6 and 12 months of follow-up, 20% and 35% of basal erosion had disappeared, respectively and of the new erosions that appeared at 6 months, 30% had disappeared 6 months later. A stastically significant association between erosion and CRP levels, entheseal Doppler signals, MASES and SPARCC was found. Conclusions: The recovery capacity of Achilles tendons in SpA seems reasonably related to formation of new bone in the enthesis area. Conclusions: US is reliable and sensitive to evaluate the presence of enthesis erosions and their changes in time, and more sensitive than X-Ray. An association was found between Achilles enthesis erosions and objective activity-based measurements of SpA outcomes. Disclosure of Interest: None Declared